The Double Dynamic Martin Screw (DMS) Adjustable Implant System for Proximal and Distal Femur Fractures - Dittel, Karl-Klaus.; Dittel, Karl-Klaus.; Rapp, Matthias.; Rapp, Matthias. (Steinkopff : Imprint: Steinkopff, 2008)
The scope and importance of hip fractures is almost incomprehensible. With a world wide incidence of close to 2 million cases per year, theses fractures pose a daunting challenge to our ability to affect and treat this epidemic. Basics for operative treatment of proximal and distal femur fractures: Clear surgical indication Short planning and preparation < 24 h Full weight bearing osteosynthesis Early mobilisation and physiotherapy In comprehensive form the book presents the usage of a meanwhile well installed implant (DMS) for osteosynthesis technique in the peritrochanteric region. The „double dynamic" stabilization (sliding tongue principle and angle adapted contoured fit) means a state of the art fracture treatment procedure. It is a convincing alternative to achieve a biological osteosynthesis at the femur. The system includes an infinitely adjustable, flexible angle, dynamic plate with a tubular distal part.